How the South African print media cover economics news: a study of inflation news in four newspapers, 1999-2001 - Kula, Momelezi Michael (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2004)
There is a considerable amount of literature arguing that economics and business journalism is growing. This subfield of journalism is important as economics issues impact on everyday lives of the people. Media have an important role to inform people about the economy and give them a voice to take part in public debates. The down side though is that economics journalism is criticised for not serving the public well in this aspect. Evidence suggests that economics journalism lost its critical character and that there is closer in economics debates. Using content analysis, this study examines coverage of inflation as reported by South African print media. Three major findings emerged: 1) Evidence shows that there are a variety of cases of inflation. 2) There are also similarities among newspapers on what they view as causing inflation. 3) However, media do not draw sources from all sectors of society. The elite, who are educated people and government officials, are over-accessed while the ordinary citizens - although also affected by inflation "“ are marginalized. Company and government sources top source lists in the media. It is argued that sources play an important role in shaping the news content. They do so by identifying problems and prescribing potential solutions. They set parameters and define terms of reference. However, media also play a mediating role. They do so by selecting sources and structuring sources in stories. They may chose to quote or report what their sources say and even comment on it. This study concludes that in South Africa ordinary citizens have no voices in economics debates. Media used bureaucratic sources only and that is a consonant agenda on inflation coverage amongst newspapers. The heavy reliance on bureaucratic sources and the exclusion of some sectors of society in sources lists raises questions about impartiality of these sources on issues relating to their organisations and institutions. These are not viable sources that could provide information that could expose abuse of power.
Keywords: Journalism, Commercial -- South Africa; Inflation (Finance) -- South Africa; South Africa -- Newspapers; Mass media -- Political aspects -- Africa; Democracy; Journalism -- Social aspects